2017
DOI: 10.3390/ijms18050930
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxytyrosol and Cytoprotection: A Projection for Clinical Interventions

Abstract: Hydroxytyrosol (HT) ((3,4-Dihydroxyphenyl)ethanol) is a polyphenol mainly present in extra virgin olive oil (EVOO) but also in red wine. It has a potent antioxidant effect related to hydrogen donation, and the ability to improve radical stability. The phenolic content of olive oil varies between 100 and 600 mg/kg, due to multiple factors (place of cultivation, climate, variety of the olive and level of ripening at the time of harvest), with HT and its derivatives providing half of that content. When consumed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
96
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 61 publications
0
96
0
1
Order By: Relevance
“…Data presented using mice fed a HFD for 12 weeks show significant decreases ( p < .05) in NF‐κB up‐regulation and NF‐κB‐dependent target expression of pro‐inflammatory genes by HT (Figure ). Considering that ROS activate NF‐κB, which in turn triggers the expression of inflammasome NLRP3 components, cytokines, chemokines and adhesion molecules, inhibition of NF‐κB signaling by HT, in association with its potent antioxidant capacity, supports the anti‐inflammatory effects of HT. Together, data reported indicate that DHA and HT co‐administration suppresses HFD‐induced liver pro‐inflammatory state by down‐regulation of NF‐κB signaling (Figure ), which is associated with the enhancement the antioxidant capacity of the liver over control values (Figure ) and supported by the significant inverse correlation established between NF‐κB DNA binding and that of Nrf2 ( r = −.90; p < .001).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Data presented using mice fed a HFD for 12 weeks show significant decreases ( p < .05) in NF‐κB up‐regulation and NF‐κB‐dependent target expression of pro‐inflammatory genes by HT (Figure ). Considering that ROS activate NF‐κB, which in turn triggers the expression of inflammasome NLRP3 components, cytokines, chemokines and adhesion molecules, inhibition of NF‐κB signaling by HT, in association with its potent antioxidant capacity, supports the anti‐inflammatory effects of HT. Together, data reported indicate that DHA and HT co‐administration suppresses HFD‐induced liver pro‐inflammatory state by down‐regulation of NF‐κB signaling (Figure ), which is associated with the enhancement the antioxidant capacity of the liver over control values (Figure ) and supported by the significant inverse correlation established between NF‐κB DNA binding and that of Nrf2 ( r = −.90; p < .001).…”
Section: Resultsmentioning
confidence: 94%
“…The latter finding is associated with decreased liver FFA influx and increased FAO that may contribute to diminish hepatic TG and VLDL synthesis . Second, the protective effects of HT in liver injury models are primarily related to its polyphenolic structure, which confers its free‐radical scavenging and metal chelating properties, therefore lowering free‐radical levels and oxidative stress status (Figure ), with the concomitant increase the antioxidant potential of the liver (Figure 5). Consequently, HT may favor FAO over de novo lipogenesis through maintenance of the basal level of n‐ 3 LCPUFAs that supports PPAR‐α (Figure ) over SREBP‐1c (Figure ) functioning.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical research have already shown that the Mediterranean diet may reduce the risk of alopecia thereby reducing the percentage of telogen and the proportion of miniaturized anagen hair . Hydroxytyrosol (HT), as a powerful antioxidant and major phenol in olive oil, presents a variety of pharmacological effects, such as antioxidant, anti‐inflammatory, and improvement of autophagy in both the pharmaceutical and cosmetic applications . It has also been shown the HT antiapoptotic effect against UVB stress in a human keratinocytes model confirming its beneficial properties and a possible application in the sun skin protection .…”
Section: Introductionmentioning
confidence: 98%